Optimal government policy : a refutation of claims that optimal policy may be time inconsistent - Walker, Paul (School of Economics, 2016)
Specifically, we are interested in the question of whether or not the supposed superiority of 'time inconsistent' policies vis-a-vis 'consistent' ones is correct. Given that the notion of 'inconsistency' forms the basis for the recent arguments in favour of 'rules' and against the use of control techniques, this question is of obvious importance. Briefly, the structure of the thesis is as follows. The first chapter concentrates on specifying the general nature of the problems tackled in the 'time inconsistency' literature, and forms the framework for the analysis which follows. Seminal papers on the issue of the 'inconsistency' of optimal plans and the inferiority of 'consistent' solutions are then examined in chapters two and three. A synthesis of the literature is reviewed in chapter four. Chapter five stands by itself as an illustration of the logical difficulties underlying claims that 'optimal' policies are in general 'time inconsistent'. The conclusion is in chapter six. Bibliography: pages 49-51.